Analisis Konflik Organisasi Sekolah dalam Perspektif Sosial dan Strategi Penyelesaiannya - Faradia Nur Ramadhani; Hauzan Ghozi Rahmawanto; Kukuh Azila Nur Hidayah; Nafita Cantika Putri; Naila Syifa u Qolbi; Yumi Hartati; Saliman Saliman (JURNAL PARADIGMA MADANI : Ilmu Sosial, Politik dan Agama, 2026)
Conflict is an inevitable phenomenon in school organizational dynamics due to interactions among individuals with diverse backgrounds, interests, perceptions, and goals. Schools as educational organizations are vulnerable to interpersonal, intergroup, and structural conflicts. This study aims to analyze school organizational conflict from a social perspective through a case study at State Senior High School 1 Tanah Putih. The research employed a descriptive qualitative approach supported by a literature review as the theoretical foundation. The findings indicate that conflicts arise from differences in communication, task distribution, leadership styles, and inconsistent interests among school members. From a social perspective, conflict is not always negative but may serve as a means of evaluation, innovation, and organizational change when managed properly. Effective conflict resolution strategies include open communication, mediation, collaboration, and strengthening a harmonious organizational culture to create a productive and conducive school climate that supports educational quality improvement.